Mutually Orthogonal Golay Complementary Sequences in Medical Ultrasound Diagnostics. Experimental Study - Ihor Trots; Norbert Żołek; Yurij Tasinkevych; Janusz Wójcik (Archives of Acoustics)
The objective of this paper is an experimental study of the most crucial parameters of the received acoustic signals (e.g. signal-to-noise ratio (SNR), side-lobes level (SLL), axial resolution) obtained as a result of simultaneous emission of mutually orthogonal Golay complementary sequences (MOGCS) to demonstrate their feasibility of being used in ultrasound diagnostics. Application of the MOGCS in ultrasound measurements allows the image reconstruction time to be shortened without decreasing the resulting quality of reconstructed images in comparison with regular complementary Golay coded sequences (CGCS). In this paper two sets of 16-bits long MOGCS were implemented in the Verasonics Vantage TM (Verasonics Inc., Kirkland, WA, USA) scanner. Ultrasound data were generated using a perfect reflector, a custom-made nylon wire phantom and tissue mimicking phantom. Parameters of the detected MOGCS echoes like SNR, SLL and axial resolution were determined and compared to that of the standard CGCS and the short two-sine cycles pulse. It was evidenced that applying MOGCS did not compromise the parameters of the separated and compressed echoes in comparison to the other types of transmitted signal – the CGCS and the short pulse. Concretely, both the MOGCS and CGCS yield similar SNR increase in comparison to the short pulse. Almost similar values of the axial resolution estimated at the full width at the half maximum level for all types of the transmitted signals were also obtained. At the same time, using the MOGCS the data acquisition speed can be increased twice in comparison with the CGCS signal.